2017
DOI: 10.1541/ieejjia.6.346
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Inverter DC Bus Voltage on the Iron Losses of a Permanent Magnet Synchronous Motor at Constant Speed

Abstract: In this paper, the impact of the DC bus voltage on the iron losses of a permanent magnet synchronous motor (PMSM) fed by a pulse-width modulation inverter is evaluated. Under constant speed operation, the modulation index decreases when the DC bus voltage increases. This modifies the harmonic content of the PMSM input voltage and then affects the motor iron losses. The experimental measurements results show that, for the conditions considered in this paper, the total iron losses are 1.8 times larger at the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…22). This result has the same trend with the ones in no-load test shown in [22]. Obviously, it is not appropriate to set a large value for V dc (e.g.…”
Section: Appendixsupporting
confidence: 76%
See 2 more Smart Citations
“…22). This result has the same trend with the ones in no-load test shown in [22]. Obviously, it is not appropriate to set a large value for V dc (e.g.…”
Section: Appendixsupporting
confidence: 76%
“…According to [22,23], once the IPMSM speed is fixed, the PWM voltage modulation index m can be adjusted by manually tuning the DC-link voltage V dc and estimated as…”
Section: Measurement Methods For Core Loss Of Ipmsmmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, m is equal to 0.241 in the no-load condition and 0.266 in the load condition. The increase of the voltage modulation index not only efficiently increases the fundamental voltage but also has the adverse effect of increasing the amplitudes of the PWM high order harmonics (9) . In this study, the effect of the higher values for the voltage modulation index on the iron losses of the motor will be presented and examined in Section 6.…”
Section: Analysis Of the Phase Voltagementioning
confidence: 99%
“…Furthermore, an analytical model has been developed to evaluate the impact of the load on the rotor iron losses of a high-speed permanent magnet synchronous motor (PMSM) (8) ; this research showed that the load can sensibly increase the rotor iron losses. Impacts of PWM voltage modulation index on motor iron losses in only the no-load condition were shown in (9) (10) . Nevertheless, the impact of the load on motor iron losses has not been enough considered.…”
Section: Introductionmentioning
confidence: 99%